Obstacles of children and adolescents with sickle cell anemia: Literature review (Research, Society and Development, 2022)
In this literature review, the obstacles that young people and children with hemoglobin S face in their daily lives will be addressed. Due to sickling of the red blood cells when there is deoxygenation, patients with sickle cell anemia suffer irreparable damage daily. There are countless discomforts, such as permanent pain in different areas of the body, complications such as stroke, priaprism, limitations in physical exercises and in case of complications and rigor in the clinical situation, blood transfusion is necessary. In this way, it is necessary that patients, parents, relatives, health and sports professionals know how to deal with events like this and what risks they run according to their daily activities. However, social inequality is notorious in Brazil, as much as the range of information is extensive, not everyone has equal access to it and often this lack of knowledge hinders the well-being and quality of life of the individual and even the social conviviality. The objective of this work is to bring more information to patients and people close to them, to know what are the biggest difficulties they face and to analyze the consequences that the lack of knowledge about sickle cell anemia can cause in an individual's life.